Radiotherapy Combined With Androgen Deprivation for Bone Oligometastases After Primary Curative Radiotherapy for Prostate Cancer: A Retrospective Study. Issue 6 (February 2016) - Wu, Jun-Xin; Lin, Li-Mei; He, Jun-Yan; Hong, Liang; Li, Jin-Luan
Abstract : Abstract: To evaluate the effects and toxicity of radiotherapy (RT) combined with androgen deprivation (AD) for bone oligometastases after primary curative RT for prostate cancer (PCa). We retrospectively analyzed 30 consecutively treated PCa patients with bone oligometastases from April 2005 to July 2014. All patients underwent RT combined with AD for oligometastatic bones after curative RT for PCa. Measured outcomes included overall survival (OS) rate, local control (LC), progression-free survival (PFS), pain relief, and toxicities. Statistical analysis was performed with SPSS17.0. The median follow-up was 32.5 months (range, 0.6–50.3). The 3-year PFS and OS rates were 22.8% (95% CI, 13.4–37.5%) and 69% (95% CI, 51.7–81.1%), respectively. The number of bone oligometastases and RT schedule were found to be significantly associated with OS on univariate analysis ( P < 0.05, respectively). The 3-year OS for patients with 1 and >1 metastases was 78.8% versus 42.2%, respectively ( P = 0.037). The long-course RT was associated with better 3-year OS compared with short-course (76.4% vs 44.1%, P = 0.03). A total of 15 (83.3%, 15/18) patients achieved pain relief. No grade 3 toxicity was observed. Long-course RT combined with ADT was effective and well-tolerated in PCa patients with bone oligometastases after curative RT for PCa. Further randomized controlled trials are needed to corroborate the findings.